Historians and Modernity - Deletić, Zdravko M.; Virijević, Vladan A. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
Modernity investigates and explains the past, according to its standards and expectations. Historians are the researchers whose results are under the surveillance of the modern national ideology, current policies, institutions, and citizens. Everybody wants to monitor and evaluate, but they honestly do not help researchers and do not appreciate professionality in the right way. The specificity of the past, its inaccessibility to direct research, lack and deficiency of the remains and sources of many research areas are objective obstacles to historical studies. It is undisputed that the outcomes of the research affects personality, knowledge, and ability of researchers, as well as their possible involvement. Impacts of ideology, politics, powerful groups, and individuals must not be neglected. The authors, based on the reference literature, research experiences, and reflections, tend to highlight some of these issues.